A Novel Energy Absorption-Based Protection Scheme for Surge Transients in Large-Scale Wind Farm System - Chen, Chen; Gao, Jiuguo; Chu, Penghao (Frontiers in Energy Research, 2022)
Onshore wind farms are usually connected to power grid by 35 kV transmission lines. Due to the high altitude of the wind turbines and associated with long transmission corridors, the lightning activities are more frequent for onshore wind farms compared to the power plant in plain areas. In addition, the insulation level of 10 to 35 kV distribution lines is general low. All these facts make the proper lightning strike protection a technical challenge to onshore wind farms. Taking a typical onshore wind farm as the testing object, the structure of the 35 kV distribution line connected to this wind farm is modelled by EMTP software in this paper. The leakage current and absorbed energy of the arrester at the head tower when lightning currents of different amplitudes inject into the overhead line are studied. By calculating the energy accumulated in the arrester within 100μs, the causes of lightning trip and damage to arrester of the distribution line, i.e., the energy accumulation mechanism, are clarified. Eventually, the lightning protection updating scheme for this distribution line is proposed in combination of refitting the porcelain cross arm at the head and end of the tower and filling the grounding body of the tower with drag-reduction agent, which shows that the lightning resistance level of the distribution can be improved by 50 times in maximum.